Play in an inclusive key. A case study - Perciavalle, Valentina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
It was investigated, through an empirical case study, the value of educational play and its inclusive value, by using the focus group as an educational research tool. A sample of students attending the Early Childhood Education laboratory of the three-year degree course in Education and Training Sciences of the University of Catania, participated in the study.